2014
DOI: 10.1002/cplu.201402240
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Graphene Oxide Nanosheets Decorated with Au Nanoparticles as an Effective Bactericide: Investigation of Biocompatibility and Leakage of Sugars and Proteins

Abstract: An efficient and simple method for selective oxidation of secondary alcohols and oxidation of alkanes to ketones is reported. An in situ prepared catalyst is employed based on manganese(II) salts, pyridine‐2‐carboxylic acid, and butanedione, which provides good‐to‐excellent conversions and yields with high turnover numbers (up to 10 000) with H2O2 as oxidant at ambient temperatures. In substrates bearing multiple alcohol groups, secondary alcohols are converted to ketones selectively and, in general, benzyl C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 72 publications
2
28
0
Order By: Relevance
“…Meanwhile, a steady decrease in I G / I D ratio with increasing laser power was observed: 1.55, 1.46, 1.04, and 0.90 for 0.03, 0.12, 0.24, and 1.30 mW, respectively. The decrease in the I G / I D ratio is in agreement with the proposed decrease in the average size of the sp 2 ‐hybridized domains in rGO–Au under laser exposure at higher powers 22. 26, 27 This observation indicates oxidation of rGO in rGO–Au under laser excitation at higher laser powers.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Meanwhile, a steady decrease in I G / I D ratio with increasing laser power was observed: 1.55, 1.46, 1.04, and 0.90 for 0.03, 0.12, 0.24, and 1.30 mW, respectively. The decrease in the I G / I D ratio is in agreement with the proposed decrease in the average size of the sp 2 ‐hybridized domains in rGO–Au under laser exposure at higher powers 22. 26, 27 This observation indicates oxidation of rGO in rGO–Au under laser excitation at higher laser powers.…”
Section: Resultssupporting
confidence: 87%
“…Moreover, the intensity of the absorption tail in the visible region for the rGO–Au NPs increased significantly compared with those of GO and GO‐Au NPs. These results are in agreement with reduction of GO to rGO, which leads to partial restoration of the aromatic network 22. The formation of Au NPs on the rGO is also supported by the presence of the SPR band at 528 nm 23…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…A matrix of GO@PEG@Ag NPs with 10 nm particle size of Ag NPs showed the highest antibacterial activity when compared to other sizes (30, 50, 80 nm The integration of gold nanostructures onto graphene-based materials has in addition been considered. 151,152,188,189 Das and co-workers showed that rGO nanosheets decorated with gold nanoparticles (Au NPs) possess high antibacterial activity; bacterial cell death is caused by the leakage of sugars and proteins from the cell membrane once in contact with the rGO-Au NPs material. 151 More recently, graphene wrapped Au nanostructures were used for the photothermal ablation of bacteria.…”
Section: Other Modified Graphene Matricesmentioning
confidence: 99%
“…It is clear that AuNPs are well dispersed with the average particle size estimated to bẽ 15 nm. [31] The reduction of GO and AuCl 4 À by ascorbic acid induces the redshift in the band from 230 nm to 265 nm, which could be assigned to the p-p* transition in GO. There is a dominant peak with the maximum at 230 nm and a shoulder at 300 nm, which is assigned to the pp* and n-p* transitions of aromatic C=C and C=O bonds respectively.…”
Section: Resultsmentioning
confidence: 99%